Technology Entrepreneurship Project (ENT 600) : Philips / Mohamad Zakwan Mohamad - Mohamad, Mohamad Zakwan (2021)
This is an attempt to find out how the theory can be applied to practical situations. As a student at UiTM Perlis, this is part of the study for all those who live project case studies. So, for this purpose, we have the opportunity to examine a company that produces a similar product that we want to develop, which is the Philips company, which is currently based in the Netherlands. First of all, general company information was collected. Information gathered through primary and secondary sources as well. The second part of this case study contains a study on a particular subject. The objective of this project is to work on the background, organizational structure, products and services, issue, problem statement, and expectations prevailing in the company and Philips products. Next, I studied about one product, namely shaver Philips Electronics. In my research on the company Philips There are some problems with the electronics Philips shaver products. Therefore, I will tell you more information to the reader in my case studies. In this case study, we analyzed the strengths, weaknesses, opportunities and threats of this company in the real business world using SWOT analysis. In addition, I will provide recommendations and conclusions in this case study.